2007
DOI: 10.1371/journal.pone.0001223
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Real-World Personal Familiarity on the Speed of Face Information Processing

Abstract: BackgroundPrevious studies have explored the effects of familiarity on various kinds of visual face judgments, yet the role of familiarity in face processing is not fully understood. Across different face judgments and stimulus sets, the data is equivocal as to whether or not familiarity impacts recognition processes.Methodology/Principal FindingsHere, we examine the effect of real-world personal familiarity in three simple delayed-match-to-sample tasks in which subjects were required to match faces on the bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 29 publications
6
43
0
Order By: Relevance
“…This finding suggests that identification is more efficient for familiar faces than unfamiliar faces. Human behavioral data also suggest that familiar faces are processed faster than unfamiliar faces for several different judgments, such as orientation, gender, and identity (Balas, Cox, & Conwell, 2007). Also, Jackson and Raymond (2006) found that familiar T2 faces were immune to the AB effect (suggesting automaticity), whereas unfamiliar faces were not (but see also Awh et al, 2004).…”
Section: Methodsmentioning
confidence: 92%
“…This finding suggests that identification is more efficient for familiar faces than unfamiliar faces. Human behavioral data also suggest that familiar faces are processed faster than unfamiliar faces for several different judgments, such as orientation, gender, and identity (Balas, Cox, & Conwell, 2007). Also, Jackson and Raymond (2006) found that familiar T2 faces were immune to the AB effect (suggesting automaticity), whereas unfamiliar faces were not (but see also Awh et al, 2004).…”
Section: Methodsmentioning
confidence: 92%
“…Behaviorally, there is a speed advantage for processing familiar versus unfamiliar faces (e.g., Balas et al, 2007). In neural terms, the rationale for examining the temporal characteristics of the response comes from studies that suggest temporally based response characteristics of the fusiform gyrus for unfamiliar and familiar faces.…”
Section: Introductionmentioning
confidence: 99%
“…All personally familiar faces have associations with an accumulation of experiences and social interactions. As they are processed frequently and repeatedly, in a range of conditions, this extensive experience is likely reflected in neural processes [Balas et al, 2007]. We wished to determine whether personally familiar faces are processed similarly to unfamiliar faces and whether there are distinct neural activation patterns across the different types of personally familiar faces.…”
Section: Introductionmentioning
confidence: 99%